Better the devil you know: Managers' networks, hiring decisions and team performance - Gwen-Jirō Clochard; Carlos Gomez-Gonzalez; Marco Henriques Pereira (Osaka University, Institute of Social and Economic Research (ISER), 2025)
Acquiring skilled workers can be a key comparative advantage for firms. However, this process involves much uncertainty that firms need to navigate. Leveraging managers' social networks can help reduce search frictions, improve match quality, and boost firm performance. In this paper, we investigate the role of managers' networks on three dimensions of individual and organizational outcomes: hiring, responsibilities, and performance. We do so by leveraging the availability of rich transactional data in professional football (soccer) in Europe. Our data covers both men's and women's football, comprising over 6k coaches, 80k players, and 100k movements between teams. First, we find that managers rely heavily on their networks for hiring decisions, particularly for non-star workers, and network-based recruiting can be done more cheaply than external hiring. Second, managers give their network-hired workers more responsibilities by allowing them more game time, particularly in the first season. Third, we find that increasing the number of network-recruited work- ers is associated with significantly higher team performance. These patterns hold consistently across both men's and women's football. We discuss the generalizability of our results and implications for managers in other industries.
Keywords: L14; J53; M51; 330; managers; network; hiring; performance; football